1980
DOI: 10.1007/bf01869117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of external cation and anion substitutions on sodium transport in isolated frog skin

Abstract: Effects of changes in external ionic strength, external cation and/or anion substitution on transepithelial influx and efflux of sodium, short-circuit current and on transepithelial potential difference and resistance were studied in isolated frog skin. Active transport of Na was found to be highly dependent on both anionic and cationic composition of external medium. Relative abilities of external monovalent cations to inhibit active Na transport were H greater than Li greater than K greater than Rb greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…1) The permeability of the luminal membrane, and therefore Na entry into the cell, is a function of the external Na concentration [32,2], or…”
Section: Discussionmentioning
confidence: 99%
“…1) The permeability of the luminal membrane, and therefore Na entry into the cell, is a function of the external Na concentration [32,2], or…”
Section: Discussionmentioning
confidence: 99%
“…In a detailed study, Biber and Mullen [6] showed that Na transport is inhibited by monovalent alkali cations and that the order of inhibition increases with decreasing ion crystal radii in accordance with Eisenman's sequences X or XI. This observation suggests the presence of a strong anionic electric field sufficient to overcome the hydration forces of the alkali cations.…”
Section: Discussionmentioning
confidence: 73%
“…Hence, the inhibitory action on Na transport might arise from the binding of Fe 3 § to negatively charged groups associated with a carrier or a charged ion channel site in the outer cell membranes and/or from modifications in general surface charge. Studies by Biber and Mullen [6], Singer and Civan [28]~ and Zeiske and Lindemann [31] have indicated that charged sites may serve as filters or binding sites for the translocation of Na across the external surface of the frog skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mannitol is commonly used to maintain total solute constant in studies of amphibian skin ion fluxes and has no apparent adverse affects (Biber and Mullen 1980).…”
Section: Bufser Solutionsmentioning
confidence: 99%